Clinical features, impulsivity, temperament and functioning and their role in suicidality in patients with bipolar disorder. (4th January 2016) - Jiménez, E.; Arias, B.; Mitjans, M.; Goikolea, J. M.; Ruíz, V.; Brat, M.; Sáiz, P. A.; García‐Portilla, M. P.; Burón, P.; Bobes, J.; Oquendo, M. A.; Vieta, E.; et al.
Abstract : Objective: Our aim was to analyse sociodemographic and clinical differences between non‐suicidal (NS) bipolar patients (BP), BP reporting only suicidal ideation (SI) and BP suicide attempters according to Columbia–Suicide Severity Rating Scale (C‐SRSS) criteria. Secondarily, we also investigated whether the C‐SRSS Intensity Scale was associated with emergence of suicidal behaviour (SB). Method: A total of 215 euthymic bipolar out‐patients were recruited. Semistructured interviews including the C‐SRSS were used to assess sociodemographic and clinical data. Patients were grouped according to C‐SRSS criteria: patients who scored ≤1 on the Severity Scale were classified as NS. The remaining patients were grouped into two groups: 'patients with history of SI' and 'patients with history of SI and SB' according to whether they did or did not have a past actual suicide attempt respectively. Results: Patients from the three groups differed in illness onset, diagnosis, number of episodes and admissions, family history, comorbidities, rapid cycling and medication, as well as level of education, functioning, impulsivity and temperamental profile. Conclusion: Our results suggest that increased impulsivity, higher rates of psychiatric admissions and a reported poor controllability of SI significantly increased the risk for suicidal acts among patients presenting SI.